THE IMPLEMENTATION OF METACOGNITIVE STRATEGY TRAINING TO ENHANCE EFL STUDENTS ORAL PRESENTATION SKILL - Panggabean, Christina Innocenti Tumiar; Triassanti, Risa (Universitas Nusantara PGRI Kediri, 2020)
Doing oral presentation has been a common classroom activity for university students including EFL students for almost any subject they are taking, but the writer found that students still had problems with their presentation and could not do their presentation effectively. In order to do the task successfully, students need metacognitive skill because they need to think about the task, plan for the task, monitor the task, and evaluate how well they have done the task. To reach this purpose, teachers need to facilitate the process through strategy instruction, especially metacognitive strategy instruction. By applying metacognitive strategies, students will be more aware of the importance of their active role in their learning. This paper is intended to present metacognitive strategy instruction adopting Oxford’ metacognitive strategies to enhance EFL students’ oral presentation skill in their speaking class and the students’ responses toward the strategy instruction. Based on the analysis of the students’ performance, video recording, teacher evaluation, self evaluation, peer evaluation, and written reflection, they have done their oral presentation better, and they had positive responses toward metacognitive instruction and became more aware of themselves as learners who are responsible for their success. Keywords: EFL students, Oral presentation skill, metacognitive strategy training